Oxidation synergistic curing material for treating high-organic-matter muck and curing method

By using oxidation co-curing materials, including solid waste-based curing agents, activators and oxidants, the problems of high organic matter content and poor engineering performance are solved, and the organic matter content is significantly reduced and engineering performance is improved, meeting the standard requirements of road base materials.

CN119638234APending Publication Date: 2025-03-18INST OF ROCK & SOIL MECHANICS CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411870880.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively reduce the organic matter content in high organic slag, resulting in poor engineering performance and difficult to meet the standard requirements of road base materials.

Method used

The oxidation synergistic curing materials are used, including solid waste-based curing agents, activators and oxidants. The oxidant is heat-activated, alkali-activated and transition metal activation complex through the activator, and combined with the secondary activation effect of the curing agent, the organic matter content is significantly reduced.

Benefits of technology

The organic matter content in high organic slag is significantly reduced, reducing it to below 5%, meeting the standard requirements of road base material, and improving the engineering performance of the cured body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses an oxidation synergistic curing material for treating high-organic-matter muck and a curing method, and belongs to the field of waste recycling and regeneration treatment. The oxidation synergistic curing material comprises a solid waste-based curing agent, an activating agent and an oxidizing agent, wherein the mass ratio of the activating agent to the oxidizing agent is 1: (4-6), and the mass ratio of the oxidizing agent to the curing agent is 1: (4-12); the solid waste-based curing agent comprises the following components in percentage by mass: 30-40% of steel slag powder, 35-45% of slag, 15-20% of fly ash and 10-20% of red mud. The activating agent comprises carbide slag and ferrous sulfate heptahydrate in a mass ratio of (4-6): 1.5; the oxidizing agent comprises sodium persulfate and sodium percarbonate in a mass ratio of (16-24): 6. The problems of high organic matter content, poor engineering performance and the like of the high organic matter residue soil are solved, the mechanical property of the cured residue soil is improved, the organic matter content can be reduced to 5% or below, and the standard requirements of road subbase materials can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of waste recycling and regeneration, and in particular relates to an oxidation synergistic solidification material and a solidification method for treating high-organic matter slag. Background Art

[0002] Construction slag is waste generated during construction due to site leveling or underground excavation, and is a type of construction waste. With the acceleration of urbanization, a large number of various types of construction waste, mainly construction slag, are generated, and many cities across the country are facing the dilemma of "slag siege". At present, the solidification and improvement of construction slag for use in construction and road engineering has become a hot topic in resource research. For example, patent CN112250412B proposes a method for treating high-viscosity slag with a curing agent prepared from granulated blast furnace slag, quicklime, sodium carbonate, sodium silicate and raw gypsum, patent CN114524660A proposes that low-carbon curing of high liquid limit muddy construction slag can be carried out using garbage incineration bottom slag, calcium carbide slag and mineral powder, and patent CN115806417B invented a curing agent with silicate cement, desulfurization ash, industrial by-product gypsum, slag powder, etc. as raw materials for curing slag.

[0003] However, some engineering slag has high organic matter problems, such as humus soil in landfills, high-organic silt slag, etc., which may cause later settlement of the project due to the degradation of organic matter when used as engineering fillers. On the other hand, organic matter will also significantly affect the strength development of cement-based materials. Conventional solidification methods cannot meet the performance requirements of the project, which makes it difficult to recycle high-organic slag resources. The main disposal methods are storage and backfilling. This disposal method not only consumes transportation costs and occupies land, but also poses safety hazards. Currently, there are few patented technologies for the disposal of high-organic slag. Patent CN117486575A proposes the use of composite bacterial mud in combination with a curing agent to dispose of high-organic slag, but the bacterial mud cultivation process is relatively complicated, and the bacterial mud decomposition cycle of organic matter is relatively long. When applied, it may be difficult to meet the limit requirements for organic matter in the relevant specifications for building and road engineering fillers.

[0004] In summary, there are still defects in the existing technology for the treatment of high-organic matter slag, such as the difficulty in quickly reducing organic matter and the poor engineering properties of solidified soil, which are technical problems that need to be solved urgently. It is necessary to develop a solidification material and solidification method for the targeted treatment of high-organic matter slag. Summary of the invention

[0005] The purpose of this application is to provide an oxidative synergistic solidification material and solidification method for treating high-organic matter slag, so as to solve the problems of high organic matter content and poor engineering performance of the slag. After solidification, the mechanical properties of the slag are improved, and the organic matter content can be reduced to below 5%, which can meet the standard requirements for road subbase materials.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] Provided is an oxidative synergistic solidification material for treating high-organic matter slag, comprising a solid waste-based solidifying agent, an activator and an oxidant; wherein:

[0008] The mass ratio of the activator to the oxidant is 1:4-6, and the mass ratio of the oxidant to the solid waste-based curing agent is 1:4-12;

[0009] The solid waste-based solidifying agent comprises, by mass percentage, 30-40% steel slag powder, 35-45% slag, 15-20% fly ash, and 10-20% red mud;

[0010] The activator comprises carbide slag and ferrous sulfate heptahydrate, and the mass ratio of the two is 4-6:1.5;

[0011] The oxidant comprises sodium persulfate and sodium percarbonate, and the mass ratio of the two is 16-24:6.

[0012] According to the above scheme, the particle size of the steel slag powder is ≤0.075mm.

[0013] According to the above scheme, the slag particle size is ≤0.075mm.

[0014] According to the above scheme, the fly ash particle size is ≤0.075mm.

[0015] According to the above scheme, the particle size of red mud is selected to be ≤0.075mm.

[0016] According to the above scheme, the particle size of carbide slag is ≤0.075mm.

[0017] A method for curing high-organic matter slag using the above-mentioned oxidation synergistic curing material is provided, comprising the following steps:

[0018] S1. The activator and the oxidant are mixed and then water is added and stirred to obtain an oxidant solution, and then the oxidant solution is added to the high organic matter soil, stirred and allowed to stand to obtain an oxidized pretreated soil;

[0019] S2. The solid waste-based curing agent is mixed with the oxidized pretreated slag obtained in step S1 to obtain a mixed material, and then statically pressed to obtain a slag solidified body.

[0020] According to the above scheme, high-organic matter slag is obtained through excavation at the construction site: the excavated engineering slag is crushed and crushed, and then sieved through a 2mm sieve. The sieved material continues to be crushed, and the above process is repeated to obtain high-organic matter slag below 2mm.

[0021] According to the above scheme, in step S1, the organic matter content in the high-organic matter slag is greater than 5%, wherein the content refers to the mass percentage.

[0022] According to the above scheme, in step S1, the standing time is 16 to 32 hours.

[0023] According to the above scheme, in step S1, the mass ratio of high-organic matter slag to oxidant is 100:2-3.

[0024] According to the above scheme, in step S2, the mass ratio of high-organic matter slag to solid waste-based curing agent is 100:9-12.

[0025] According to the above scheme, the mass ratio of the dry weight of the mixed material obtained in step S2 to the water added in step S1 is 100:14-18.

[0026] According to the above scheme, in step S2, the solidified body is subjected to standardized curing for more than 7 days.

[0027] The present invention provides an oxidation-coordinated solidification material for high-organic soil, which aims to solve the problem of high organic matter content and poor engineering performance in high-organic soil by synergistically coordinating the components in the oxidant and the curing agent; the specific mechanism is as follows:

[0028] Sodium persulfate and sodium percarbonate are used as oxidants, and carbide slag and ferrous sulfate heptahydrate are used as activators to activate the oxidants (see reaction formulas 1 to 3 for the activation reaction process of the main oxidant sodium persulfate); carbide slag can play the role of alkali-activated oxidant on the one hand, and release a large amount of heat after dissolving in water to play the role of thermal activation on the other hand; ferrous sulfate heptahydrate plays the role of transition metal-activated oxidant, and through the combined action of thermal activation, alkali activation and transition metal activation, it promotes the production of SO4-· and OH· free radicals with strong redox effects in the environment, which can effectively remove lignin in organic matter, but the removal efficiency of humus is not obvious. The introduction of the curing agent will change the surface potential of the soil particles, and the free radicals will exist more on the surface of the soil particles, realizing the secondary activation effect on the oxidant, promoting the oxidative free radicals in the environment from being dispersed in the solution to being surface-bound free radicals, thereby promoting the removal of humus. Therefore, through the synergistic action of the oxidant, the activator and the curing agent, the organic matter content is significantly reduced to below 5%, meeting the application standard of road curing soil.

[0029] S2O8 2- (Heating) → 2SO4 - Reaction 1

[0030] SO4 - +OH - →SO4 2- +OH· Reaction 2

[0031] S2O8 2- +Fe2+ →SO4 - +SO4 2- +Fe 3+ Reaction 3

[0032] At the same time, the sulfate ions and carbonate ions generated by the oxidant of the present invention promote the hydration reaction of the cementitious material, react with the slag, fly ash, steel slag and other materials in the curing agent to generate hydration products such as ettringite and calcium carbonate, enhance the skeleton structure and matrix density, and provide the required strength of the solidified body to optimize the engineering performance. In addition, the composite oxidant effectively avoids the problem of excessive sulfate ion concentration caused by the use of sodium persulfate alone, and improves the organic matter removal efficiency and engineering performance.

[0033] The beneficial effects of the present invention are as follows:

[0034] 1. The present invention provides an oxidative synergistic solidification material for high-organic matter slag, which significantly improves the removal effect of the oxidant on lignin through the combined action of thermal activation, alkali activation and transition metal activation of the oxidant by the activator; combined with the secondary activation effect of the curing agent on the oxidant, the occurrence form of oxidative free radicals is optimized, and the removal of humus is promoted; ultimately, the efficient removal of organic matter in high-organic matter slag is achieved, and the organic matter content is reduced to below 5%, meeting the application standards for road solidification soil; at the same time, the sulfate ions and carbonate ions generated by the oxidant reaction promote the hydration reaction of the curing agent component, thereby enhancing the skeleton structure and the density of the matrix, and promoting the improvement of the engineering properties of the solidified body.

[0035] 2. The present invention provides a method for solidifying high-organic matter slag, which first pre-treats the high-organic matter slag with an activator + oxidant to preliminarily remove organic matter (especially lignin); then adds a curing agent to achieve secondary activation of the oxidant to further remove organic matter (especially humus); the obtained solidified body has excellent engineering performance and stability, effectively eliminating the engineering defect of traditional curing agents that are affected by their high organic matter and lead to poor curing effect, and at the same time reduces the organic matter content of the solidified soil mixture to a reasonable range, and can be used as a material for roadbed filling, foundation pit backfilling, etc., and consumes large amounts of solid waste such as steel slag and slag, etc., with significant environmental and economic benefits. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in combination with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0037] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0038] The embodiment of the present invention provides an oxidation-synergistic solidification material and method for high-organic matter slag, and the overall idea is as follows:

[0039] S1. The high-organic slag obtained from the construction site is air-dried, crushed with a jaw crusher, and the crushed slag is sieved through a 2mm sieve. The sieved material continues to be crushed, and the above process is repeated to obtain high-organic slag with a particle size of less than 2mm. The purpose of the above process is to make the particle size of the slag uniform;

[0040] S2, preparing the selected carbide slag and ferrous sulfate heptahydrate in a specified mass ratio to obtain an activator, and preparing the selected sodium persulfate and sodium percarbonate in a specified mass ratio to obtain an oxidant. The activator and the oxidant are mixed and stirred, then added into water and stirred evenly to obtain an oxidant solution, and then the oxidant solution is added into the high-organic matter slag obtained in step S1, stirred evenly and then allowed to stand to obtain oxidized pretreated slag;

[0041] S3. The selected slag, steel slag, fly ash and red mud are weighed according to the mass ratio of slag and soil, mixed and stirred evenly to obtain a solid waste-based curing agent. The slag, steel slag powder, fly ash and red mud are all ≤0.075mm.

[0042] S4, mixing the curing agent with the oxidation pretreated slag to obtain a mixed material, and then performing static pressure molding to obtain a slag solidified body for curing at room temperature.

[0043] In the static pressure forming, the mass ratio of water to the mixed material needs to be controlled near the optimal moisture content of the mixed material. In this embodiment, based on the test data of the pretreated slag, the overall mass ratio of water to the dry weight of the mixed material is controlled to be 0.17:1.

[0044] The following will describe in detail an oxidative synergistic solidification material and solidification method for treating high-organic matter slag in the present application in combination with examples, comparative examples and experimental data.

[0045] Example 1

[0046] Provided is a method for curing high-organic matter slag using an oxidation-cooperative curing material, wherein the oxidation-cooperative curing material comprises an oxidant, an activator and a solid waste-based curing agent; wherein:

[0047] The mass ratio of the oxidant to the activator is 4:1; the oxidant includes sodium persulfate and sodium percarbonate, and the mass ratio of the two is 4:1; the activator includes carbide slag and ferrous sulfate heptahydrate, and the mass ratio of the two is 4:1;

[0048] The mass fraction ratio of each component in the solid waste-based solidifying agent is 30% of steel slag powder, 45% of slag, 15% of fly ash, and 10% of red mud;

[0049] The mass ratio of oxidant, solid waste-based solidifying agent and high-organic matter slag is 2:9:100.

[0050] The curing method specifically comprises the following steps:

[0051] S1. The high-organic slag obtained from the construction site is air-dried, crushed by a jaw crusher, and sieved through a 2mm sieve. The sieved material is crushed again, and the above process is repeated to obtain high-organic slag with a diameter of less than 2mm; wherein the organic matter content of the obtained high-organic slag with a diameter of less than 2mm is 10.9%.

[0052] S2, prepare the selected calcium carbide slag (particle size ≤ 0.075mm) and ferrous sulfate heptahydrate in a specified mass ratio to obtain an activator, and prepare the selected sodium persulfate and sodium percarbonate in a specified mass ratio to obtain an oxidant. Mix the activator and the oxidant, then add them into water and stir them evenly to obtain an oxidant solution, then add the oxidant solution into the high-organic slag with a thickness of less than 2mm obtained in step S1, stir them evenly and let them stand for 24 hours to obtain oxidation pretreated high-organic slag;

[0053] S3. The selected slag, steel slag, fly ash and red mud are weighed according to the mass ratio of slag and soil, mixed and stirred evenly to obtain a solid waste-based curing agent. The particle sizes of the slag, steel slag powder, fly ash and red mud are all ≤0.075mm.

[0054] S4, mixing the curing agent with the oxidation pretreated slag to obtain a mixed material, wherein the mass ratio of the amount of water added in step S2 to the dry weight of the mixed material is 0.17:1, and then performing static pressing to obtain a slag solidified body for curing at room temperature.

[0055] Example 2

[0056] A method for treating high-organic matter slag using an oxidation synergistic solidification material is provided. The specific steps are the same as those in Example 1, except that the mass ratio of the oxidant, the solid waste-based solidifying agent and the high-organic matter slag in the oxidation synergistic solidification material is 2:12:100.

[0057] Example 3

[0058] A method for treating high-organic matter slag using an oxidation synergistic solidification material is provided. The specific steps are the same as those in Example 1, except that the mass ratio of the oxidant, the solid waste-based solidifying agent and the high-organic matter slag in the oxidation synergistic solidification material is 3:12:100.

[0059] Comparative Example 1

[0060] Provided is a solidification method for treating high-organic slag using ordinary Portland cement, wherein the mass ratio of ordinary Portland cement to high-organic slag is 12:100, and the method comprises the following steps:

[0061] S1. The high-organic slag obtained from the construction site is air-dried, crushed with a jaw crusher, and sieved through a 2mm sieve. The sieved material continues to be crushed, and the above process is repeated to obtain high-organic slag with a size of less than 2mm.

[0062] S2. Mixing ordinary Portland cement with the high-organic matter slag obtained in step S1 to obtain a mixed material, adding water and performing static pressure molding, wherein the mass ratio of water to the mixed material is 0.17:1, and obtaining a slag solid body for curing at room temperature.

[0063] Comparative Example 2

[0064] Provided is a method for treating high-organic matter slag using oxidizing materials, wherein the oxidizing materials only use an activator and an oxidizing agent, and no curing agent is used, wherein: the oxidizing agent includes sodium persulfate and sodium percarbonate, and the mass ratio of the two is 4:1; the activating agent includes carbide slag and ferrous sulfate heptahydrate, and the mass ratio of the two is 4:1; the mass ratio of the oxidizing agent to the activating agent is 4:1, and the mass ratio of the oxidizing agent to the high-organic matter slag is 3:100.

[0065] The curing method comprises the following steps:

[0066] S1. The high-organic slag obtained from the construction site is air-dried, crushed with a jaw crusher, and sieved through a 2mm sieve. The sieved material continues to be crushed, and the above process is repeated to obtain high-organic slag with a size of less than 2mm.

[0067] S2, the selected carbide slag and ferrous sulfate heptahydrate are prepared according to the mass ratio to obtain an activator, and the selected sodium persulfate and sodium percarbonate are prepared according to the mass ratio to obtain an oxidant. The activator and the oxidant are mixed and stirred, and then added into water and stirred evenly to obtain an oxidant solution, and then the oxidant solution is added into the high organic matter slag of less than 2 mm obtained in step S1, stirred evenly and then allowed to stand for 24 hours, and then statically pressed, wherein the mass ratio of water to the dry weight of the mixed material is 0.17:1, and a slag body sample is obtained.

[0068] Comparative Example 3

[0069] Provided is a solidification method for treating high-organic slag soil using solidification materials. The solidification material only uses a solid waste-based solidifying agent, and does not use an activator or an oxidizing agent. The mass fraction ratio of each component in the solid waste-based solidifying agent is 30% of steel slag powder, 45% of slag, 15% of fly ash, and 10% of red mud; and the mass ratio of the solid waste-based solidifying agent to the high-organic slag soil is 12:100.

[0070] The following steps are involved:

[0071] S1. The high-organic slag obtained from the construction site is air-dried, crushed with a jaw crusher, and sieved through a 2mm sieve. The sieved material continues to be crushed, and the above process is repeated to obtain high-organic slag with a size of less than 2mm.

[0072] S2. The selected slag, steel slag, fly ash and red mud are weighed according to the mass ratio of slag and soil, mixed and stirred evenly to obtain a solid waste-based curing agent. The slag, steel slag powder, fly ash and red mud are all ≤0.075mm.

[0073] S3. Mix the curing agent in step S2 and the high-organic matter slag obtained in step S1 to obtain a mixed material, add water and perform static pressure molding, wherein the mass ratio of water to the mixed material is 0.17:1, and obtain a solidified slag body and cure it at room temperature.

[0074] Comparative Example 4

[0075] A method for curing high-organic matter slag using an oxidation synergistic curing material is provided. The specific steps are the same as those in Example 1, except that the mass ratio of the oxidant, the curing agent and the high-organic matter slag in the oxidation synergistic curing material is 1:6:100.

[0076] Comparative Example 5

[0077] A method for treating high-organic matter slag using an oxidation synergistic solidification material is provided. The specific steps are the same as those in Example 1, except that the mass ratio of the oxidant, the solid waste-based solidifying agent and the high-organic matter slag in the oxidation synergistic solidification material is 1:12:100.

[0078] Related experiments and data:

[0079] The solidified slag products obtained in each embodiment and comparative example were subjected to relevant performance tests:

[0080] 1. Unconfined compressive strength: The samples were prepared using the static pressure method with a cylindrical sample of 39.1 mm*80 mm. The 7d and 28d unconfined compressive strengths of the solidified slag samples were measured in accordance with the Geotechnical Test Method Standard (GBT50123-2019). The results are shown in Table 2.

[0081] 2. Organic matter content: The content was determined by potassium dichromate oxidation method. The test process was in accordance with NY / T 1121.6-2006 Soil Testing Part 6: Determination of Soil Organic Matter. The results are shown in Table 2. At the same time, the test showed that the organic matter content of the high organic matter slag soil with a thickness of less than 2 mm used in the embodiments and comparative examples was 10.9%, which was relatively high and did not meet the requirements of GB50202-2018 "Construction Quality Acceptance Standard for Building Foundation Engineering".

[0082] 3. Organic matter composition: The soil humus composition tests the content of humic acid, fulvic acid and humin in the soil. The experimental process is determined according to the "Determination of soil humus composition by sodium pyrophosphate-sodium hydroxide extraction and potassium dichromate oxidation capacity method" NY / T1867-2010. In addition, the content of lignin, cellulose and hemicellulose in the soil is supplemented. The lignin test method is to use acetyl bromide to dissolve the lignin in the sample, and then determine the total lignin content by colorimetry. Both cellulose and hemicellulose are tested quantitatively by concentrated acid hydrolysis sugar determination method. Trifluoroacetic acid is used to hydrolyze cellulose and hemicellulose in the sample, and the cellulose content is determined by reaction with anthrone colorimetric agent under strong acid conditions. The organic matter composition of the high-organic matter slag below 2 mm used in the embodiments and comparative examples is mainly humus (0.22% humic acid, 0.38% fulvic acid and 3.09% humin), 6.11% lignin, 0.27% hemicellulose, and 0.34% cellulose. The organic matter composition results of the embodiments and comparative examples are shown in Table 2.

[0083] Table 1. Performance analysis of the cured products obtained in Examples 1-3 and Comparative Examples 1-5

[0084]

[0085] Table 2. Analysis of organic composition of the solidified bodies obtained in Examples 1-3 and Comparative Examples 1-5

[0086]

[0087]

[0088] From the data in Table 1 and Table 2, we can see that:

[0089] Comparing Example 1 and Example 2, it can be seen that as the amount of curing agent increases, the organic matter content decreases, indicating that the curing agent also helps to improve the organic matter removal effect of the oxidant. On the one hand, this is because the increase of the curing agent increases the environmental pH, which helps the sodium persulfate to undergo oxidation reaction in the system, and on the other hand, the calcium hydroxide and other components contained in the curing agent itself consume a small part of the organic acid. In addition, the addition of the curing agent will produce a secondary activation effect on the oxidant, promoting the conversion of oxidative free radicals in the environment from being dispersed in the solution to surface-bound free radicals, thereby promoting the removal of humus.

[0090] The ordinary Portland cement in comparative example 1 has limited consumption and removal of organic matter in the slag, which is still above 9%, and cannot meet the application standard requirements of engineering fillers; at the same time, the curing effect on the slag is significantly weaker than the oxidation-synergistic low-carbon solid waste-based curing agent proposed in the present invention, mainly because the high organic matter environment has a significant negative impact on the hydration reaction of ordinary Portland cement. In terms of engineering properties, the 7d unconfined compressive strength of the cured slag with 12% of ordinary Portland cement by mass of the slag is only 1.56MPa, which is lower than the unconfined compressive strength when the curing agent content in the oxidation-synergistic curing method in Example 1 is 9% of the slag mass; compared with Example 2, although the curing agent content is 12%, the 7d and 28d unconfined compressive strengths of Example 2 are improved by 52.6% and 36.8% respectively compared with comparative example 1, indicating that the oxidation-synergistic curing materials and methods effectively improve the engineering performance of the cured body.

[0091] Compared with Example 3 and Comparative Examples 2-3, the synergistic use of the oxidant and the curing agent can more effectively remove organic matter in high-organic matter slag, making its total organic matter content less than 5%, meeting the standard requirements for road subbase materials.

[0092] Although the preferred embodiments of the present invention have been described in detail, those skilled in the art are fully capable of further adjusting and improving these embodiments after understanding and mastering the basic innovative concepts of the present invention. Therefore, the appended claims are intended to cover not only the preferred embodiments listed, but also all reasonable changes and modifications based on the concept of the present invention, as long as they still fall within the essential scope of the present invention.

[0093] In other words, the connotation of the present invention is not limited to the specific embodiments disclosed, but should include those situations that, although different changes and modifications are made by those skilled in the art to the present invention, still remain consistent with the spirit of the present invention and the scope of protection of the claims. Therefore, the scope of protection of the present invention application is not limited to the specific embodiments presented here, but should be understood to cover all implementation forms in the broadest sense that are consistent with the principles and innovative features described in this application.

Claims

1. An oxidation synergistic solidification material for treating high-organic matter slag, characterized in that: It includes solid waste-based curing agent, activator and oxidant; among which: The mass ratio of the activator to the oxidant is 1:4-6, and the mass ratio of the oxidant to the solid waste-based curing agent is 1:4-12; The solid waste-based solidifying agent comprises, by mass percentage, 30-40% steel slag powder, 35-45% slag, 15-20% fly ash, and 10-20% red mud; The activator comprises carbide slag and ferrous sulfate heptahydrate, and the mass ratio of the two is 4-6:1.5; The oxidant comprises sodium persulfate and sodium percarbonate, and the mass ratio of the two is 16-24:

6.

2. The oxidation-synergistically solidified material according to claim 1, characterized in that: The particle size of steel slag powder is ≤0.075mm; the particle size of slag is ≤0.075mm; the particle size of fly ash is ≤0.075mm; the particle size of red mud is ≤0.075mm; the particle size of calcium carbide slag is ≤0.075mm.

3. A method for curing high-organic matter slag using the oxidation synergistic curing material according to claim 1, characterized in that: The following steps are involved: S1. The activator and the oxidant are mixed and then water is added and stirred to obtain an oxidant solution, and then the oxidant solution is added to the high organic matter soil, stirred and allowed to stand to obtain an oxidized pretreated soil; S2. The solid waste-based curing agent is mixed with the oxidative pre-treated slag obtained in step S1 to obtain a mixed material, and then statically pressed to obtain a slag solidified body.

4. The curing method according to claim 3, characterized in that: In step S1, the high-organic matter slag is obtained by repeatedly rolling and crushing the engineering slag obtained from the construction site and then screening it to 2 mm.

5. The curing method according to claim 3, characterized in that: In the step S1, the organic matter content in the high-organic matter slag is above 5%.

6. The curing method according to claim 3, characterized in that: In the step S1, the standing time is 16-32 hours.

7. The curing method according to claim 3, characterized in that: In the step S1, the mass ratio of the high-organic matter slag to the oxidant is 100:2-3.

8. The curing method according to claim 3, characterized in that: In the step S2, the mass ratio of high-organic matter slag to solid waste-based curing agent is 100:9-12.

9. The curing method according to claim 3, characterized in that: The mass ratio of the dry weight of the mixed material obtained in step S2 to the water added in step S1 is 100:14-18.

10. The curing method according to claim 3, characterized in that: In the step S2, the solidified body is left to stand and be cured for more than 7 days.

Citation Information

Patent Citations

  • A method for solidifying high-viscosity slag for use as backfill material

    CN112250412B

  • Low-carbon curing method for high-liquid-limit mucky engineering muck

    CN114524660A